NUTRITION APPLICATION TO SUPPORT FITNESS IN AMPUTEE FOOTBALL ATHLETES - Akbar Harmono, Bayu; Mulyono, Mulyono; Bripandika Putra , Ismawandi; Hayati, Hayati; Natanael Keryapi, Cristian; Surya Pratama, Dani; Sulaiman Choiri, Ahmad (Journal of Social Comunity Services, 2025)
Objective: This study aims to identify the challenges faced by athletes, particularly those with disabilities, in implementing proper training and nutrition management programs. It highlights the importance of structured nutritional strategies in enhancing physical fitness, improving performance, and supporting recovery for football players. Method: The research employs a community development practice approach, focusing on providing training and nutritional education to disabled football athletes. These initiatives were designed to increase awareness and encourage the adoption of balanced nutrition and hydration practices during training and competition. Results: The program successfully improved athletes' knowledge of the significance of balanced nutrition and proper hydration. However, further efforts are required to ensure the optimal implementation of nutrition programs that fully support athletes' physical fitness and performance. Novelty: This study addresses a specific gap by focusing on disabled athletes in football, an area often overlooked in sports nutrition research. It emphasizes the role of structured nutritional management in enabling athletes to achieve peak performance, reduce injury risks, and compete at higher levels.